Vitamin B12 Deficiency Among A Mendelian Population Of North India (Applied Biological Research, 2018)
Prevalence of vitamin B12 deficiency has increased in community in recent  time. The present study was done to assess vitamin B12 status with respect to  age and sex. Vitamin B12 assays were performed on 1512 individuals from a  North Indian Lacto vegetarian community and further validated on a familial sample of 79 individuals. Individuals were considered to be  , if vitamin B12 levels were
Keywords: Culture; dietary habits; gender; lifestyle; vegetarianism; vitamin B12 deficiency